If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2xsquared + 18 + 28 Reorder the terms: 0 = 18 + 28 + 2adeqrsux Combine like terms: 18 + 28 = 46 0 = 46 + 2adeqrsux Solving 0 = 46 + 2adeqrsux Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2adeqrsux' to each side of the equation. 0 + -2adeqrsux = 46 + 2adeqrsux + -2adeqrsux Remove the zero: -2adeqrsux = 46 + 2adeqrsux + -2adeqrsux Combine like terms: 2adeqrsux + -2adeqrsux = 0 -2adeqrsux = 46 + 0 -2adeqrsux = 46 Divide each side by '-2deqrsux'. a = -23d-1e-1q-1r-1s-1u-1x-1 Simplifying a = -23d-1e-1q-1r-1s-1u-1x-1
| 9x+x-2x+8=4x | | 5y-2x=33 | | 40x+15(1.5x)=2115 | | 33.6=4x/2 | | ln(x-15)+(x+48)=3ln(4) | | 2(x+12)=3x+24 | | y=15+3 | | 16=t(t-6) | | 5y+7y=24 | | 52.5=15x | | 3h=0.3h+0.075 | | y-0.6=-2.4 | | 0.25d+0.5=12 | | z^2-(3+3i)=0 | | 3x^3+16x+5= | | 288(564)=752(x) | | 3/w-14=10 | | -2=x/4+1 | | (3x-2)(6x+12)= | | 4(x+7.5)=40 | | 5x+7=39x-8 | | 35+10+8x=61 | | w+0.625=0.5 | | 24q-64=8q | | 4x-36=2x-12 | | -2+12=m-1 | | 18=18+2x | | log^4(x+2)=log^4(55) | | 12-4x+0.6x^2=11.3 | | 12-4x+0.6x^2=0 | | 5-x/2=21 | | 8x-(5-(4x+7))=26 |